2017
DOI: 10.1016/j.eururo.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Complications After Systematic, Random, and Image-guided Prostate Biopsy

Abstract: Evidence Synthesis: The most frequent complication after PB is minor and self-limiting bleeding (hematuria and hematospermia), irrespective of the biopsy approach. Occurrence of rectal bleeding was comparable among traditional TRUS-guided and image-guided PB. Almost 25% of patients experience lower urinary tract symptoms, but only a few have urinary retention, with higher rates after transperineal approach. Temporary erectile dysfunction is not negligible, with a return to baseline after 1-6 months. The incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
311
5
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 403 publications
(395 citation statements)
references
References 83 publications
19
311
5
14
Order By: Relevance
“…TRB carries a small but clinically significant and increasing risk of sepsis. TPB, whether MRI-targeted or not, consistently results in zero or near-zero rates of serious infection (1). Furthermore, it has now been shown that fluoroquinolones or other combinations of broad-spectrum antibiotics are not necessary for prophylaxis in TPB.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TRB carries a small but clinically significant and increasing risk of sepsis. TPB, whether MRI-targeted or not, consistently results in zero or near-zero rates of serious infection (1). Furthermore, it has now been shown that fluoroquinolones or other combinations of broad-spectrum antibiotics are not necessary for prophylaxis in TPB.…”
Section: Discussionmentioning
confidence: 99%
“…Each needle passage risks inoculating the prostate and its rich blood supply with rectal bacteria. As a “dirty” procedure, prophylactic antibiotics are necessary and fluoroquinolones are currently recommended as the antibiotics of choice (1,13). However, there are three major concerns regarding the widespread use of fluoroquinolones in TRB.…”
Section: Mri-targeted Transrectal Biopsy (Trb)mentioning
confidence: 99%
See 3 more Smart Citations